Penegakan Hukum Terhadap Penambangan Liar - Wika, Sarita; Wirasila, Anak Agung Ngurah (Kertha Wicara : Journal Ilmu Hukum, 2020)
Mining sector is a business that has an important role as an additional source of state income , but the existence of those can also cause problems in the environmental sector, one of the mining businesses that can cause environmental problems is illegal mining. The Illegal mining activities  has met the element of punishment for the perpetrator, therefore law enforcement is needed to protect the sustainability of the environment. The purpose of this paper is to examine law enforcement against illegal mining. The research method used is normative research, where the results of this study is law enforcement for illegal mining actors can be subject to criminal penalties under Article 158 of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mining Mineral and Coal, that prison penalty and fine penalty will be applied.   Keywords: illegal mining, criminal act, law enforcement.